Entrepreneurship Development Centres and Employment Generation in Lagos State, Nigeria - Ijiola, Oluwabukola; Nwogwugwu, Ngozi (NIU Journal of Humanities; Vol 8 No 2 (2023): NIU Journal of Humanities, Vol. 8 No. 2, June 2023DO - 10.58709/niujhu.v8i2.1653, 2023)
University environments naturally foster innovation, the free interchange of ideas, and fresh perspectives on the world. Entrepreneurship has become a faster-growing academic topic since universities have embraced it. Entrepreneurship for students in the higher institution is designed to inspire and create an innovative mindset for students. This mindset will provide the students with the ability and vision to transfer opportunities into wealth. In spite of all these efforts, the statistics on the tremendous rise in jobless rates in Nigeria suggest that the country is on its way to becoming the world unemployment capital. This paper, therefore, examined the role of entrepreneurship centers in achieving employment generation in Lagos State, Nigeria. The population of the study was 36,774 students from two selected universities in Lagos State. A sample of 456 students was selected from both universities using Cochran’s formula. The study found that Entrepreneurship Centers had a significant effect on youth empowerment in Nigeria (β = 0. 49, t = 11.58, p < 0.05). Entrepreneurship Centers had a significant effect on employment generation in Nigeria (β = 0.59, t = 11.58, p < 0.05). The findings underscore the importance of fostering a supportive ecosystem for entrepreneurs through access to finance, mentorship programs, and collaboration between stakeholders. The recommendations emphasize the need to invest in skills development, enhance access to technology and infrastructure, address regulatory challenges, and encourage research and data collection. By implementing these recommendations, Nigeria can leverage entrepreneurship to drive sustainable and inclusive economic growth. Keywords:   Entrepreneurship center, Entrepreneurship Education, Employment generation, Youth empowerment